Marxism recycled. - Van Parijs, Philippe; Elster, Jon; Roemer, John (Cambridge : University Press Editions de la Maison des Sciences de l'Homme, 1993)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: 20e eeuw